Developing model of vocational skill learning management to prepare mild mentally retarded children in entering the world of work - Rejo Kirono; Sunardi Sunardi; Suparno Suparno; Lantip Diat Prasojo (Faculty of Education, Universitas Negeri Yogyakarta, 2018)
This study aims: (1) to map the practice of skill learning management in several special schools recently; (2) to gain information of things needed in developing the skill learning model (3) to create vocational skill learning management model to prepare mild mentally retarded children in entering the world of work; (4) and to find out information of the model effectiveness. The design of this research and development broadly comprises three phases: (1) the preliminary study covering the literature study, the arena study,(2) questionnaire distribution and need analysis through the FGD with 30 headmasters, 102 teachers and 33 parents from 33 special schools in Yogyakarta as the research subject; (3) the model development including the formulation of the model, validation of the model draft by 14 practitioners (headmaster and teacher) and 10 experts, and the revision of the model; and (4) the limited testing by 6 practitioners, the small group testing by 12 practitioners, the extended testing by 33 practitioners, and final model revision. Data analysis uses descriptive statistical analysis techniques and descriptive qualitative analysis. The results show that: 1) the practice of vocational skill learning management in special schools recently outlining following evidences (a) the skill material is not appropriate to the needs of DUDI (World of Business and Industry), (b) study group classification is based on the class grade, (c) thematic learning approach is in line with the skill themes, (d) the use of drilling methods, (e) learning evaluation is oriented on the result, (f) has not organized field practice (PKL) and job training yet, (g) schools have not established cooperation with parents and DUDI yet, and (h) the headmasters have not fully implemented the management function. 2) the needs of model development are (a) vocational skill material selection based on the need of DUDI; (b) study group classification based on the types of skill; (c) thematic learning approach based on the skill themes; (d) the use of drilling methods; (e) learning evaluation on the process and result; (f) organizing field practice and job training; (g) establishing cooperation with parents and DUDI; (h) the charismatic headmasters who have a lot of ideas are able to implement the function of management in vocational skill learning. 3) The resulting model are (a) vocational skill material selection based on the need of DUDI; (b) study group classification based on the types of skill; (c) thematic learning approach based on the skill themes; (d) the use of drilling methods; (e) learning evaluation on the process and result; (f) organizing field practice and job training; (g) establishing cooperation with parents and DUDI; (h) the charismatic headmasters who have a lot of ideas are able to implement the function of management in vocational skill learning. 4) The result of model content testing in very good category and the result of model applicability testing in very good category.